The effect of Lactobacillus casei extract on cervical cancer cell lines - Kim, Soo-Nyung; Lee, Won Moo; Park, Kyoung Sik; Kim, Jong Bin; Han, Dae Jong; Bae, Jaeman (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : Lactobacillus casei ( L. casei ) has been shown to inhibit the proliferation of several types of cancer in vivo , but its effect on cervical cells has not been reported. We incubated cells of the human cervical cell lines Caski and HeLa with extracts of L. casei and investigated its effects on the growth of the cells and possible synergy with anticancer drugs. Material and methods : Cell-free extracts of L. casei were prepared and purified. Cultures of Caski and HeLa cells adhering to tissue culture plates were treated with L. casei extract. The effects of L. casei extract on the growth of cancer cells and its possible synergy with anti-cancer drugs in cervical cancer cell lines were investigated. The cells were treated with L. casei extract alone, anti-cancer drugs alone [doxorubicin, paclitaxel, 5-fluorouracil (5-FU), and cisplatin], or L. casei extract plus anti-cancer drugs. Results : L. casei extract had no significant effect on the growth rate of the two cell lines. Anti-cancer drugs alone induced growth inhibition, but there was no synergistic effect of L. casei extract on growth inhibition. Conclusions : L. casei extract does not have a potent effect on the viability of cervical cancer cells in vitro . In addition, L. casei extract has no synergistic effect on the inhibition of growth of cancer cells in the presence of anti-cancer drugs.